Penguasaan Morfologi dalam Menulis Artikel Populer - Olin Nita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to describe the mastery of morphology in writing popular articles. This research uses a quantitative approach with the correlation method. The sample of this study was the students of the Indonesian Language and Literature Study Program STKIP Abdi Pendidikan Payakumbuh Foundation in 2016, amounting to 13 people. The results of the study, 1) mastery of student morphology in general is in the range of 86-95% with excellent qualifications, 2) popular article writing skills in general students are in the range of 76-85% with good qualifications, 3) the relationship of morphology mastery with writing skills popular student articles with r values ​​of 0.5738. After being analyzed with the t-test formula, the value of tcount> ttable is 2.2155> 1.812 with dk n-2 (12-2 = 10) and a significance level of 0.05 or 95%. Conclusion, there is a significant relationship between the mastery of morphology to the skills of writing popular articles Keywords: Morphology, Skills, Popular Article Writing.